(untitled) (Raparin Journal of Humanities (RJH), 2023)
The languages that spoken on the earth are between growth and decay, for this it has many factors. The type of destruction dependent on historical circumstances. (Baker, 2003) assumes that, as a historical result of the confrontation of two nations in two very specific circumstances in combining elements of the two languages and creating a new language, The Morphological differences play a role in the resistance of languages to extinction, When they neighbor each other while they have different morphological classes (for example, Kurdish and Arabic). Therefore, for the above reasons, it is often more favorable to preserve the language in all its dialects than to try to standardize it. This research is entitled (The spread of dialects and languages between branching and fading in the light of botany). The foundations of this idea belongs to the views of botanists about the way plants grow in relation to different environments. Converting this idea to the field of dialectology appeared by the linguist (Hudson). Linking this model to plant developments in different environments is the focus of analysis in this model, and the research delves into its explanations in some linguistic phenomena and manifestations that have not been addressed in previous models and theories, such as the separation of dialects from their languages, and the remaining of speakers of a dialect in a confined area, far removed from its dialect or their original language? Can languages in their speakers’ resistance in linguistic conflicts, be likened to the secretions that plants produce in the face of all the dangers and pests that pose a danger in their growth process and in different environments? The research tries to answer all the questions، that have been closed to satisfactory solutions.